PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PEMALSUAN SURAT KETERANGAN DOKTER UNTUK MENYESATKAN PENGUASA (STUDI PUTUSAN NO. 600/PID.B/2021/PN SDA).: Criminalization of Perpetrators of the Crime of Falsifying Doctor’s Certificates to Mislead Officials (Decision Study No. 600/Pid.B/2021/PN SDA). - Firdaus, Azhar; Masjhur, Fauzy (AMICUS CURIAE, 2024)
Article 263 paragraph (1) of the Criminal Code Jo. Article 55 paragraph (1) of the Criminal Code in general explains that if the defendants are proven together to have forged a letter intended to be a sign of a matter or event, and distribute it to those who need the letter, they will be subject to imprisonment for 2 years. In reality, this type of agreement is often carried out by perpetrators of criminal acts in similar fields. So the problem is which provisions the Panel of Judges can apply in carrying out appropriate sentencing. Data processing is carried out qualitatively, while drawing conclusions is carried out usinglogical deduction or logical reasoning. The results of the study illustrate that 1) according to the provisions of the decision, based on decision Number 600/Pid.B/2021/PN.SDA with the case of letter forgery mode, according to the provisions of Article 263 as the law which is the basis of the decision, it is appropriate, namely the four defendants jointly The same has fulfilled the requirements as stated in the article including facts of confession, evidence of falsified letters and received a maximum sentence of 2 years. 2) Consideration of the panel of judges in sentencing, basically the application of article 263 paragraph (1) of the Criminal Code Jo article 55 paragraph (1) of the Criminal Code has been fulfilled, but there is an element that the judge did not pay attention to, namely falsification of a doctor’s certificate, so that the use of this article is not appropriate . So the right article should be used is article 268 of the Criminal Code.